Curriculum Development for Al-Qur'an Hadith Subjects in Islamic School - Dama, Kiman; Yahiji, Kasim; Ondeng, Syarifuddin; Arif, Muh (Journal La Edusci, 2024)
This research is a type of field qualitative research and uses descriptive analysis methods. The data obtained from this research are KMA documents, interviews, and excerpts from various relevant literary sources, especially those related to the issues raised. The data collection technique is in the form of literature review which is carried out in the following way: reading various literature and providing assistance with quotations related to Al-Qur'an Hadith Subject Curriculum Development in Madrasas Based on KMA no 183 and 184. Analysis and description are analysis techniques used on data related to Al-Qur'an Subject Curriculum Development an Hadith at the madrasa. This study aims to provide an explanation regarding the Development of the Al-Qur'an Hadith Subject Curriculum at m. Decree of the Minister of Religion (KMA) number 183 concerning Islamic and Arabic religious education curricula and KMA number 184 of 2019 concerning guidelines for implementing curriculum in madrasas to improve and become a legal umbrella in developing the distinctiveness of madrasas, developing character strengthening, anti-corruption education and developing religious moderation at the madrasah.